TU1.7 The correlation between BITE score and weight outcomes in Mini/One Anastomosis Gastric Bypass patients – an update with 24-month post-operative results. (9th August 2022) - Gurunath, Tharun Muthu; Edwards, Olivia; Sufi, Pratik; Parmar, Chetan
Abstract: Background: The Bulimic Investigatory Test, Edinburgh (BITE) self-report questionnaire is used to assess the risk of bulimic and binge eating habits in bariatric patients preoperatively. This study aimed to investigate the correlation between preoperative BITE scores and weight loss at 3, 6, 12, 18 and 24 months follow up in patients with Mini-Gastric Bypass (MGB-OAGB). Method: Consecutive patients who received MGB-OAGB between 2016–2018 completed the BITE questionnaire at initial assessment and were included in this prospective study. Baseline demographics were measured. Excess body weight loss (%EBWL) and total weight loss (%TWL) were calculated on the day of surgery and at 3, 6, 12, 18 and 24 months follow up. Results: 120 patients were eligible with an average age of 43 (± 10.84) years. 21.67% (n=26) had high BITE scores (≥20), 44.17% (n=53) had medium BITE scores (10–19), and 34.17% (n=41) had low BITE scores (≤9). Low and Medium BITE groups had similar outcomes at each follow up. The low BITE group had greater %EBWL and %TWL compared to high BITE group across all the follow ups, however this difference was not significant. There were no reoperations or mortality. Conclusion: MGB-OAGB results in good weight loss at 3, 6 and 12 months post-operatively independent of BITE scores. There was no significant difference between pre-operative binge eating behaviours on post-operative weight outcomes. To extend the study, further research between the effect of pre-operative psychological input on weight outcomes could be investigated. Going forward, comparative study in patients with RYGB and sleeve gastrectomy would be recommended.